Influence test of Averrhoa Bilimbi leaf extract as denture cleanser on the growth of Streptococcus Mutans - Dewi Kristiana; Depi Praharani (Universitas Padjadjaran, 2011)
It has been believed for a long time, especially by Indonesian people, that Averrhoa Bilimbi leaves have medical efficacy. Streptococcus mutans (S. mutans) are bacteria mostly found in plaque. The plaque on denture may cause inflammation in a mucosal tissue under the denture namely denture stomatitis. This study was aimed at observing the differences of Averrhoa Bilimbi leaf extract efficacy as denture cleanser in a concentration of 4%, 8%, 16% for 15 minutes, 30 minutes, 1 hour, dan 8 hours on the growth of S. mutans. The samples were made from heat-cured resin acrylic plates with the dimension of 10x10x1 mm. Heat-cured resin acrylic plates were immersed in Averrhoa Bilimbi leaf extract with the concentration of 4%, 8%, 16% for 15 minutes, 30 minutes, 1 hour, dan 8 hours which each concentration contained 8 samples, and heat-cured resin acrylic plate was immersed in the aquades as the control. To observe the inhibiting force of Averrhoa Bilimbi leaf extract on the growth of S. mutans, it was tested using the spectrometer. The data were analyzed using one-way ANOVA. The result showed that there were significant differences (p< 05). Then the data were analyzed using LSD test and it showed that there were significant differences on heat-cured resin acrylic plates immersed in Averrhoa Bilimbi leaf extract with the concentration of 4%, 8%, 16% for 15 minutes, 30 minutes, 1 hour, dan 8 hours on the growth of S. mutans. In conclusion, Averrhoa Bilimbi leaf extract in the concentration of 16% used to immerse the acrylic plate for 8 hours effectively inhibited the growth of S. mutans.